Should the paradigms of banking theory be redefined based on banking practice? (Thoughts on the polarity of opinion concerning the polish banking sector) - Jan Szambelańczyk; Monika Marcinkowska (e-Finanse: Financial Internet Quarterly, 2016)
In accordance with the principles of best academic practice, a research community is identified through an internalised paradigm comprising notions and theories that form the foundations of a given academic field or discipline. This paper aims to provide a selective overview of differing opinions with respect to solutions, phenomena or processes concerning the Polish banking sector, as an example of the degree of development of banking theory and practice. In view of the analysis a question arises as to whether finance and socio-economic practice holds a paradigm that would prove adequate in terms of the level of development of such practice, i.e. the so-called disciplinary matrix, involving symbolic generalisations, informational efficiency of financial markets hypothesis), methodological assumptions (reflecting the cognitive structure of the phenomena, processes or structures researched) or, finally, models for resolving scientific problems (handbooks, monographs, research reports) and practical experience (e.g. methods of arbitration valuation, estimating the risk premium). Or perhaps, as G. Ko±odko would put it, the finance paradigm is really based on the fact that 'things happen the way they do, because many things are happening all at once'. It cannot be ruled out that what finance needs is a change similar to the economics of complexity, defined by A. Wojtyna as the incorporation of a behavioral concept (reconstructing the homooeconomicus concept) and challenging the tradional understanding of economic system equilibrium and dynamics. It is also worth considering whether the triad of finance categories (money, risk, time) is not lacking a fourth component, namely trust, essential for financial stability and the balance between finance capital and social capital, serving as the basis for efficient financial intermediation (including the development of an unselfish advisory function, especially with regard to financial products securing the customers' day-to-day existence in the post-employment period).
Keywords: G00; G21; L25; 330; banking theory; bank performance; Polish banking sector